HUBUNGAN KETERAMPILAN POLA ASUH HOLISTIK DENGAN PERKEMBANGAN ANAK - Tri Sunarsih; Astuti, Endah Puji; Shanti, Elvika Fit Ari (Universitas Islam Negeri Alauddin Makassar, 2024)
The first five years is a very short period and cannot be repeated, so it is often called the